Mechanism Underlying the Shading-Induced Chlorophyll Accumulation in Tea Leaves - Chen, Jiaming; Wu, Shuhua; Dong, Fang; Li, Jianlong; Zeng, Lanting; Tang, Jinchi; Gu, Dachuan (Frontiers in Plant Science, 2021)
Besides aroma and taste, the color of dry tea leaves, tea infusion, and infused tea leaves is also an important index for tea quality. Shading can significantly increase the chlorophyll content of tea leaves, leading to enhanced tea leaf coloration. However, the underlying regulatory mechanism remains unclear. In this study, we revealed that the expressions of chlorophyll synthesis genes were significantly induced by shading, specially, the gene encoding protochlorophyllide oxidoreductase (CsPOR). Indoor control experiment showed that decreased light intensity could significantly induce the expression of CsPOR, and thus cause the increase of chlorophyll content. Subsequently, we explored the light signaling pathway transcription factors regulating chlorophyll synthesis, including CsPIFs and CsHY5. Through expression level and subcellular localization analysis, we found that CsPIF3-2, CsPIF7-1 and CsHY5 may be candidate transcriptional regulators. Transcriptional activation experiments proved that CsHY5 inhibit CsPORL-2 transcription. In summary, we concluded that shading might promote the expression of CsPORL-2 by inhibiting the expression of CsHY5, leading to high accumulation of chlorophyll in tea leaves. The results of this study provide insights into the mechanism regulating the improvements to tea plant quality caused by shading.